Limited Motor Vehicle Production : hearings before the United States House Committee on Interstate and Foreign Commerce, Subcommittee on Commerce and Finance, Ninetieth Congress, second session, on Jan. 30, 1968. (U.S. Congressional Hearings., 1968)
Committee Serial No. 90-24. Considers H.R. 8457 and similar S. 2029, to amend the National Traffic and Motor Vehicle Safety Act to authorize exemptions from motor vehicle safety regulations for vehicles produced in limited numbers.